National macrofinancial stability in the context of cyber threats - Zhyvylo , Yevhen (Pressing Problems of Public Administration, 2024)
This article addresses the critical issue of ensuring state macrofinancial stability in the face of growing cyber threats. Financial market stability forms the foundation of any country’s economic development and prosperity, as it ensures efficient capital movement, reduces uncertainty, and promotes investment growth. However, this stability is vulnerable to various external and internal threats, particularly cyber risks, which can significantly disrupt financial institutions’ operations and even cause serious economic turmoil. The author emphasizes the critical importance of this issue in the era of digital economic transformation, where financial systems become increasingly vulnerable to potentially catastrophic consequences of cyberattacks. The article analyzes the main channels through which cyber incidents impact financial stability, including payment system disruptions, loss of investor and consumer confidence, and critical service failures due to the interconnectedness of financial institutions. Special attention is paid to cyber readiness challenges in developing countries, which often lack sufficient resources and experience to effectively counter digital threats. The author emphasizes the necessity of developing and implementing comprehensive national cybersecurity strategies that would define clear objectives, priorities, and mechanisms for protecting financial infrastructure. These strategies should be based on global best practices and encompass a wide range of measures: from establishing an effective regulatory framework to investing in human capital development. The article also emphasizes the importance of enhancing international cooperation to strengthen cyber resilience, considering the cross-border nature of digital threats. In this context, the key role of global institutions, such as the International Monetary Fund, in providing technical assistance to countries, conducting training, and developing universal cyber risk assessment tools is noted. Overall, the article contributes to the study of financial sector cybersecurity issues and offers the author’s vision for addressing them at both national and international levels.